Strategi Pemasaran Agen Untuk Mencapai Target Perusahaan Dengan Penjualan Produk Asuransi Umum Pada PT. Asuransi Umum Bumiputera Muda Cabang Medan - Silvia Retri Aldona Tampubolon; Fauzi Arif Lubis (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Abstract This study aims to analyze the marketing strategies carried out by agents in achieving company targets by selling general insurance products at PT Asuransi Umum Bumiputera Muda Medan Branch. This research was conducted by conducting interviews with insurance agents operating in the branch. The results showed that agents use various marketing strategies to achieve the sales target of general insurance products. The strategies carried out are SWOT Analysis Strategy and identifying potential target markets, building good relationships with prospective customers, making persuasive presentations, providing clear and accurate information about products, and providing good service to customers. In addition, agents also use marketing media such as social media and personal networks to expand the reach of product promotion. The results of this study are expected to contribute to the development of general insurance agent marketing strategies to achieve company targets and increase sales of general insurance products. Keywords : Strategy, Insurance Agen, Targets